An urban planning sustainability framework: Systems approach to blue green urban design. (March 2021) - Puchol-Salort, Pepe; O'Keeffe, Jimmy; van Reeuwijk, Maarten; Mijic, Ana
Highlights: Theoretical framework incorporating blue-green solutions in the urban planning system. Urban natural capital evaluation, providing a common language for urban stakeholders. Quantification of urban natural capital indicators using a GIS tool. Case study showcasing the framework's sustainable design approach. Abstract: The climate emergency and population growth are challenging water security and sustainable urban design in cities worldwide. Sustainable urban development is crucial to minimise pressures on the natural environment and on existing urban infrastructure systems, including water, energy, and land. These pressures are particularly evident in London, which is considered highly vulnerable to water shortages and floods and where there has been a historical shortage of housing. However, the impacts of urban growth on environmental management and protection are complex and difficult to evaluate. In addition, there is a disconnection between the policy and decision-making processes as to what comprises a sustainable urban development project. We present a systems-based Urban Planning Sustainability Framework (UPSUF) that integrates sustainability evaluation, design solutions and planning system process. One of the features of this master planning framework is the spatial representation of the urban development in a Geographical Information System to create an operational link between design solutions and evaluation metrics. UPSUF moves from an initial baseline scenario to a sustainable urban development design, incorporating the requirements of governance and regulatory bodies, as well as those of the end-users. Ultimately, UPSUF has the potential to facilitate partnership between the public and the private sectors.